Fracture of the Bone Inducing Its Necrosis as the End Point in the Evolution of Untreated Neuroarthropathy - Dured Dardari; Alfred Penfornis (Medicina, 2021)
We describe here the case of a female patient with type I diabetes who developed active Charcot neuroarthropathy in the foot. Due to therapeutic noncompliance, talus necrosis was discovered 2 years after the presentation of neuroarthropathy. The impact of untreated neuroarthropathy on the bone is commonly described as fracture and joint dislocation, but we describe the complete disappearance of the bony structure and its necrosis associated with active neuroarthropathy in a patient who refused offloading.